"A New Reality of Harlem": Imagining the African American Urban Future during the 1960s. (27th June 2017) - MATLIN, DANIEL
Abstract : Envisioning Harlem's future served as a particularly vivid means of addressing the dilemmas posed by the prospect of desegregation. Should black peoplehood – in part a legacy of oppression and racialization – persist in a post-segregation era? This article calls for greater attention to be paid to the visions of future existence that animated, and were animated by, the black freedom struggles of the 1960s. It explores contrasting architectural reimaginings of Harlem and argues that ideas about existing black places and the nature of their built environment were important factors in shaping commitments to, and idealizations of, both integrationist and black nationalist futures.